Anthropogenic influences on Cd, Cr,Cu, Ni, Pb and Zn concentrations in soils and sediments in a watershed with sugar cane crops at São Paulo State, Brazil - Conceição, F. T. [UNESP]; Navarro, G. R B [UNESP]; Silva, A. M. [UNESP] (My University, 2013)
The use of fertilizers NPK and amendments in sugar cane crops may change the heavy metals concentrations in soils, making them available for plants and, consequently, they can be transferred to the human food chain. This study describes the redistribution of heavy metals (Cd, Cr, Cu, Ni, Pb and Zn) in soils with sugar cane crops due to fertilizers NPK and amendments at Corumbataí River basin, São Paulo State. The heavy metals concentrations were determined in samples of fertilizers NPK (5:25:25) and amendments (limestones, KCl, and phosphogypsum) by atomic absorption spectrometry (AAS). Heavy metals incorporated in fertilizers NPK and amendments are annually added in the sugar cane crops, but if utilized in accordance with the recommended rates, they do not raise the concentration levels in soils up to hazards values. Those applications promote the decrease of heavy metals concentration in soils profiles with sugar cane crops due to their fractionation to water soluble and/or exchangeable fractions, and the results still indicate that the profiles do not possess hazard levels in relation to heavy metals concentration. In relation to metals concentration in a sediment core, Cu, Ni, Pb and Zn values increased progressively from 1974 to 2000 due to anthropogenic activities, mainly sugar cane crops, indicating adverse biological effects to the aquatic environment and to organisms living in or having direct contact with sediments.
Keywords: Crops; Environmental; Fertilizers; Geochemistry; cadmium; chromium; concentration (composition); copper; crop production; crop yield; fertilizer application; lead; nickel; soil amendment; soil chemistry; sugar cane; watershed; zinc; Brazil; Sao Paulo [Brazil]